Massive retrosternal goitre presenting with hypertension. Issue 6 (November 1972) - Holden, M. P.; Wooler, G. H.; Ionescu, M. I.
Abstract : A patient presented to her doctor with dyspnoea on exertion. Hypertension was diagnosed and she was subsequently found to have a large retrosternal goitre. The blood pressure returned to normal after the tumour had been removed. To our knowledge no such case has previously been reported. Early removal of mediastinal tumours is advocated.